Genome-Wide Investigation of N6-Methyladenosine Regulatory Genes and Their Roles in Tea (Camellia sinensis) Leaves During Withering Process - Zhu, Chen; Zhang, Shuting; Zhou, Chengzhe; Xie, Siyi; Chen, Guangwu; Tian, Caiyun; Xu, Kai; Lin, Yuling; Lai, Zhongxiong; Guo, Yuqiong (Frontiers in Plant Science, 2021)
N6-methyladenosine (m6A), one of the internal modifications of RNA molecules, can directly influence RNA abundance and function without altering the nucleotide sequence, and plays a pivotal role in response to diverse environmental stresses. The precise m6A regulatory mechanism comprises three types of components, including m6A writers, erasers, and readers. To date, the research focusing on m6A regulatory genes in plant kingdom is still in its infancy. Here, a total of 34 m6A regulatory genes were identified from the chromosome-scale genome of tea plants. The expansion of m6A regulatory genes was driven mainly by whole-genome duplication (WGD) and segmental duplication, and the duplicated gene pairs evolved through purifying selection. Gene structure analysis revealed the sequence variation contributed to the functional diversification of m6A regulatory genes. Expression pattern analysis showed that most m6A regulatory genes are differentially expressed under environmental stresses and tea-withering stage. These observations indicated that m6A regulatory genes play essential roles in response to environmental stresses and tea-withering stage. We also found that RNA methylation and DNA methylation formed a negative feedback by interacting with each other's methylation regulatory genes. This study provided a foundation for understanding the m6A-mediated regulatory mechanism in tea plants under environmental stresses and tea-withering.